PREVALENCE OF MEDIAL CALCANEAL NEUROPATHY,CAUSE HEEL PAIN IN GIRLS WHO WEARS HIGH HEELS - Shinde , Miss. Sakshi; DURGAWALE, DR. ANKITA (South Eastern European Journal of Public Health, 2024)
BACKGROUND : In this topic there is prevalence of calcanealneuropathy which causesPain in the plantar heel is a frequent issue that can be very uncomfortable chronic plantar heel pain has been linked to a number of neurological Etiology including entrapment neuropathy of the medial calcaneal nerve a branch of the posterior tibial nerve. One kind of tarsal tunnel syndrome is through to be medial calcaneal neuropathy. OBJECTIVE : The study was done to determine the prevalence of medial calcaneal neuropathy which causes heel pain. METHODS: The study was an observational study which include 357 girls in Karad which includes rural and urban area. Consent forms was explained and signed by the participants. The test performed was specific to neuropathy Tinel’s sign. RESULT : on the basis of the study 84.5 girls has pain and 15.5 girls is not having pain in both urban and rural area . CONCLUSION : The study concluded that there is a significant portion of individuals with persistent plantar heel pain have medial calcaneal neuropathy.